2021
DOI: 10.1007/s43678-020-00013-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of frequent users of emergency departments in Alberta and Ontario, Canada: an administrative data study

Abstract: Objective Frequent users to emergency departments (EDs) are a diverse group of patients accounting for a disproportionate number of ED presentations. This study examined sociodemographic and ED visit characteristics of adult high-system users in two Canadian provinces. Methods Cohorts of high-system users were created for Alberta and Ontario including patients with the top 10% of presentations in the National Ambulatory Care Reporting System (April 2015-March 2016). Controls were random samples of non-high-sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Most of the studies on frequent ED users were performed outside Canada. A recent study identified patients’ characteristics associated with frequent ED use in Alberta and Ontario [ 4 ]. However, this study was based on administrative data, without health-related variables.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on frequent ED users were performed outside Canada. A recent study identified patients’ characteristics associated with frequent ED use in Alberta and Ontario [ 4 ]. However, this study was based on administrative data, without health-related variables.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, seven studies found females were higher resource users than males and six found that sex-based differences were dependent upon other factors. Females were identified as higher resource users in multiple health care settings, including health services for all ages [16,17,21,22,28], health services for youth [29,30], primary care for all ages, and adult emergency department presentations [21,31].…”
Section: Sexmentioning
confidence: 99%
“…Three studies used comorbidity scores or indices -ie. the Charlson Comorbidity Index (CCI) -to determine the burden of comorbidities [16,17,21,22,28,32]. Patients with higher scores on the comorbidity indices were more likely to be hospitalized [28] and to see primary care and specialist visits [17].…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Characteristics of frequent users of emergency departments in Alberta and Ontario, Canada: an administrative data study, Rosychuk et al [1] conducted a broad, thorough and impressive population-based study of individuals who are high-frequency ED users in two Canadian provinces, which are home to approximately 20 million Canadians. Their paper characterizes important demographic and clinical information, which may inform localized interventions and policy creation by provincial ministries, health systems and community providers.…”
mentioning
confidence: 99%